Comparative aspects of volatile fatty acid production in reindeer Rangifer tarandus tarandus) in northern Norway and on South Georgia - Mathiesen, Svein D.; Sørmo, Wenche; Utsi, Tove H. Aagnes (Rangifer, 2000)
Dietary influence on pH and volatile fatty acids concentrations and production rates in the rumen and distal fermentation chamber (DFC) was investigated in Norwegian reindeer (Rangifer t. tarandus) on South Georgia in summer (SG), and in northern Norway in late summer (NS) and winter (NW). Mean [standard deviation (s)] ruminal pH was similar in SG teindeet (6.46, s = 0.13) and NW reindeer (6.45, s = 0.19), but significantly different from NS reindeer (6.87, s = 0.08)(P < 0.05). Mean DFC pH in SG reindeer (6.92, s = 0.12) and in NS reindeer (6.70, s = 0.16) did not differ significantly. In NW reindeer DFC pH (6.26, s = 0.20) was significantly lower than in the SG and NS animals (P < 0.05). Mean ruminal concentration of volatile fatty acids (VFA) was 92.4 mM (s = 13-3) in SG reindeer, which was significantly larger (P < 0.05) than in NS (71.5 mM, s = 10.2) and NW reindeer (73.3 mM, s = 9.7). In DFC mean VFA concentration was 51.3 mM (s = 11.7), and 48.8mM (s = 14.5) in SG and NW reindeer respectively, and significantly less than in NS reindeer (86.7mM, s = 5.4) (P < 0.05). Mean daily ruminal VFA rate of production was 246.4 kj/kg BM"" in SG teindeer, compared to 195.6 kj/kg BM"" in NS and 193.4 kJ/kgBM0 75 in NW reindeer. Mean daily VFA rate of production in DFC was 8.3 kj/kg BM0 75 in SG reindeer compared to 6.2 kj/kg BM07' in NS and 3.0 kj/kg BM"75 in NW reindeer. The summer pastures on SG and NS were of moderate quality in terms of ruminal VFA production. In winter in northern Norway when forage quality was assumed to be low, both ruminal and DFC pH were low. The high fermentation rate in winter was probably due to easily digestible carbohydrates in the lichens eaten. DFC seems to be of minor importance in these reindeer in terms of VFA energy yield.